Moral Problems and MothersÔÇÖ Efforts to Educate Children in Single Parent Families - Fatli Ashari, Lastri; Anwar, Fuady (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
Family has a crucial responsibility to give the basic and foremost educations that determine childrenÔÇÖs moral in the future. This study aims to find out the moral problems of children from single parent families and mother's efforts to educate the children. This was qualitative research using case study design. Data were collected by carrying out in-depth interviews to ten selected informants using purposive sampling technique. Data analysis referred to Miles and HubermanÔÇÖs. Overall, the study found eight childrenÔÇÖs moral problems that were categorized into two aspects, they were obedience (ignoring parents) and personality problems such as gambling, fighting, stealing, being promiscuous, being badly affected by online game, lying, and dating. To overcome the moral problems, single mothers did three ways to educate their children, namely giving advice, exemplary, and punishment.